(untitled) (Update Dental College Journal, 2022)
This study examined the pretreatment and post treatment dental arch width changes between the extraction and non-extraction cases in Angle’s class I patients. Sixty pre-treatment and post-treatment dental casts from 30 extractions and 30 non-extractions participants were selected for the study. The inter-canine and inter-molar maxillary arch width were measured by Vernier gauge caliper. An unpaired t-test was performed to evaluate the arch width changes between extraction and non-extraction groups. The results showed that inter-molar and inter-canine maxillary arch widths in the non-extraction group were slightly higher than those in the extraction group in both pre- and post-treatment, but the differences were not statistically significant. In conclusion, the extraction and non-extraction techniques used in orthodontic treatment did not change the inter-caning and inter-molar arch widths. Update Dent. Coll. j: 2022; 12(2): 24-26